OPTIMALISASI UKS DALAM PENANGANAN KEGAWATDARURATAN DI SEKOLAH MELALUI PELATIHAN KEGAWATDARURATAN DASAR - Chanif -; Maryam -; Sri Widodo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The Position of red cross personnel in school trained in prehospital stage in an integrated system of emergency response (SPGDT) has a very strategic position. The victim's condition requiring the airway clear, adequacy of pulmonary ventilation, blood circulation is good and avoid further bleeding and protected from disability becomes an important point that a first helper must have an adequate scientific basis on skills Patient Emergency Response. The school is one of the educational institution as a place to learn the students gain knowledge. Various circumstances in the school environment could trigger the arrival of emergency medical service that can not be estimated time for example a storied school building, a slippery floor can be at risk of risk of injury. It is necessary a safe community concept in the school environment such as in SMA 1 and SMK Muhammadiyah Semarang. This study aims to describe the knowledge of emergency first aid in members of the red cross at each school. The methodology in this study is descriptive study with number of subject is 44. Result of the study showed that the average score of knowledge before and after is 46 and 63 respectively. If members of red cross dealing with emergency cases of trauma and non-trauma or in the school environment should be able to provide first aid by using the steps appropriate action. To achieve this, the participants were given training First Emergency Aid Course (EFAC), basic emergency equipment procurement tool in each school and development activities in a sustainable manner.Key words: Training, emergency first aid course, red cross